A Descriptive Study On The Implementation Of The 2013Curriculum In Teaching English At The Seventh Grade Of SMP Negeri 5 Sragen In 2014 / 2015 Academic Year - Purbosari, Wahyu; , Dr. Dwi Haryanti, M. Hum; , Drs. Djoko Srijono, M. Hum (2015)
The objective of this study is to describethe procedure in teaching English and to describe the evaluation system in teaching English using the 2013 Curriculum at the seventh grade of SMP Negeri 5 Sragen in 2014 / 2015 academic year. This research is descriptive research. The method of collecting data is direct observation, interview, and document. In technique for analyzing data is reducing the data, displaying the data, and drawing conclusion and proposing suggestion. The result shows that: (1) there are three teaching objectives in teaching English using the 2013 Curriculum, namely: the learners are able to use the English language orally and written in daily behavior, the teacher introduces English lesson as a foreign language that is important in the future, and the learners can develop their competency in English language that covers attitude (spiritual attitude and social attitude), knowledge, and skill; (2) The syllabus that is used by the teacher as reference in making lesson plan is designed by the government; (3) the teacher makes the lesson plan before teaching her students. One lesson plan can be used for one or more meetings. The teacher has an authority to develop the lesson plan that is suitable with the material and the learner's characteristic; (4) the teacher holds eleven roles. Those roles are the teacher as the monitor, motivator, controller, instructor, director, transformative agent, and constructor of knowledge, actor, model, innovator, and evaluator; (5) the learners hold six roles. Those roles are the learners as the subject and object of learning, planner, communicator, performer, resource of learning, and evaluator; (6) the teacher uses the textbook that is produced by the government. Besides, the teacher also uses dialogue, realia, teacher's knowledge, dictionary, the learner's information, and internet as the learning resources. The teacher uses dialogue as the media for teaching her students; (7) the classroom activities, the teacher adopts the scientific approach that consists of five steps, namely: observing, questioning, collecting information, associating, and communicating; (8) the method of teaching is inquiry-based learning; (9) the classroom activities are suitable with the lesson plan; (10) the evaluation system, the teacher uses authentic assessment to evaluate the learners. The teacher gives an evaluation in three aspects. Those aspects are attitude (spiritual and social), knowledge, and skill.